The Role of Job Satisfaction Mediation on the Influence of Perceived Organizational Support and Work Discipline on Employee Organizational Citizen Behavior in Tabanan Regency - I Dewa Gede Pramuditya Trenggana PUTRA; I Made SARA; A. A. Media MARTADIANI (PT Keberlanjutan Strategis Indonesia, 2025)
Bali, as a leading tourist destination, faces intense competition in the hospitality industry, particularly among three-star hotels in Tabanan Regency, which have experienced significant growth. However, challenges such as low organizational citizenship behavior (OCB), job satisfaction, work discipline, and organizational support persist. Limited communication, lack of appreciation, and inadequate managerial supervision hinder employee performance. This study aims to analyze the mediating role of job satisfaction in the relationship between perceived organizational support and work discipline on OCB. The research involves 180 employees from five three-star hotels in Tabanan Regency as the population. Using the Yamane (Slovin) formula with a 5% margin of error, a sample size of 124 employees was obtained. The sampling technique used is proportional stratified random sampling, ensuring that the sample distribution aligns with the number of employees in each hotel to maintain representativeness. The hypothesis was tested using inferential analysis with Partial Least Squares (PLS). The results indicate that perceived organizational support and work discipline have a positive but insignificant influence on organizational citizenship behavior (OCB). Conversely, both variables have a positive and significant effect on job satisfaction. Additionally, job satisfaction has a positive and significant impact on OCB and serves as a mediating variable in the relationship between perceived organizational support and work discipline on OCB, highlighting that job satisfaction is a crucial factor in enhancing OCB.